Belonging to the Army : Camp Followers and Community during the American Revolution - Mayer, Holly A. (Holly Ann), 1956- (Book collections on Project MUSE., 1996)
"Belonging to the Army reveals the identity and importance of the civilians now categorized as camp followers, whom Holly A. Mayer calls the forgotten revolutionaries of the War for American Independence. These merchants, contractors, family members, servants, government officers, and military employees provided necessary supplies, services, and emotional support to the troops of the Continental Army. They served in virtually every imaginable capacity, from lifting spirits with food, drink, and dances to nursing the sick, digging ditches, and spying on and fighting against the enemy. Mayer demonstrates that by making encampments livable communities - a matter of some significance given the years it took to achieve independence - these civilians played a fundamental role in the survival and ultimate success of the Continental Army."--Jacket.